Comparison of hemodynamic responses along with perfusion index to tracheal intubation with Macintosh and McCoy laryngoscopes - Choudhary, Vineet K.; Rastogi, Bhawana; Singh, V. P.; Ghalot, Savita; Dabass, Vijay; Ashraf, Sameer (International Journal of Research in Medical Sciences, 2018)
Background: The McCoy Laryngoscope in comparison to macintosh laryngoscope requires less force for performing laryngoscopy and as a result may alter the associated hemodynamic response. Perfusion index (PI) is a noninvasive numerical value of peripheral perfusion obtained from a pulse oximeter. Methods: A randomized prospective single blind comparative clinical study was conducted on 80 patients of ASA physical status I-II aged between 18 years to 58 years of either sex with body mass index (B.M.I) between 20 and 25 undergoing elective surgeries under general anesthesia. 80 patients were divided into 2 groups: Group A (n=40)- Tracheal Intubation with Macintosh Laryngoscope, Group B (n=40)-Tracheal Intubation with McCoy Laryngoscope. Blood Pressure (systolic blood pressure, diastolic blood pressure, and mean arterial pressure) and heart rate (HR), oxygen saturation (SpO2) via pulse oximeter were monitored. Results: The demographic profile showed no significant difference between the groups. Heart rate, systolic, diastolic and mean arterial pressure had highly significant difference in both groups. Perfusion index was statistically significant immediately post laryngoscopy and intubation till 4 mins. Immediately after laryngoscopy and intubation, the correlation between PI and MAP was statistically significant and it was a negative average to good correlation. Conclusions: The McCoy laryngoscope elicits lesser haemodynamic response to laryngoscopy and tracheal intubation as compared to Macintosh laryngoscope in normotensive patients. Perfusion index can also serve as an additional parameter to assess hemodynamic response since it has good negative correlation with the mean arterial pressure.